Earth construction: A changing tradition - Jooste-Smit, Petria (Acta Structilia, 1998)
In the recent past, this age-old construction technique has been transformed through thorough research, the application of scientific methods and innovative experimentation. Today this traditional system has a much more sophisticated application, has a longer life span, looks modern and may accommodate all the modern amenities that Africa’s people strive for. We may benefit from this method of construction in South Africa since it may contribute towards the empowerment and development of local people through the development of skills, the provision of job opportunities and the limitation of building costs, since local materials are used. The opportunity is thus created to live in harmony with the environment, whilst evoking memory and identity.